2021
DOI: 10.1101/2021.01.19.426900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In VivoSubcellular Mass Spectrometry Enables Proteo-Metabolomic Single-cell Systems Biology in a Chordate Embryo Developing to a Normally Behaving Tadpole (X. laevis)

Abstract: We present the first example of in vivo high-resolution mass spectrometry (HRMS) for subcellular molecular systems biology of proteins and metabolites. With light microscopy, we identified the left-dorsal and left-ventral animal cells in cleavage-stage non-sentient Xenopus laevis embryos. Using precision-translated fabricated microcapillaries, the subcellular content of each cell was double-probed, each time collecting <5% of cell volume (~10 nL) swiftly (<5 s/event). The proteins and metabolites were an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 42 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…The goal of this study was to integrate electrophysiology with single-cell HRMS proteomics. Our recent work adapted in situ , and in vivo capillary microsampling to microanalytical CE-ESI-HRMS platforms to enable direct proteomics and metabolomics in large, identified cells (∼500 to 250 μm diameter) in developing chordate embryos. These instruments preserved cell and embryonic viability, allowing for evaluations of anatomy and whole-organismal behavior .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The goal of this study was to integrate electrophysiology with single-cell HRMS proteomics. Our recent work adapted in situ , and in vivo capillary microsampling to microanalytical CE-ESI-HRMS platforms to enable direct proteomics and metabolomics in large, identified cells (∼500 to 250 μm diameter) in developing chordate embryos. These instruments preserved cell and embryonic viability, allowing for evaluations of anatomy and whole-organismal behavior .…”
Section: Resultsmentioning
confidence: 99%
“…Our recent work adapted in situ , and in vivo capillary microsampling to microanalytical CE-ESI-HRMS platforms to enable direct proteomics and metabolomics in large, identified cells (∼500 to 250 μm diameter) in developing chordate embryos. These instruments preserved cell and embryonic viability, allowing for evaluations of anatomy and whole-organismal behavior . In a series of studies, we also found the technology scalable to smaller cells and other functional measurements, including electrical recording of neuronal activity. This report captures the development, testing, and validation of this technology following the systematic approach outlined in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations